RadioJockey: Mining Program Execution to Optimize Cellular Radio Usage - Athivarapu, Pavan Kumar; Bhagwan, Ranjita; Guha, Saikat; Navda, Vishnu; Ramjee, Ramachandran; Arora, Dushyant; Padmanabhan, Venkat; Varghese, George (In Proceedings of the 18th Annual International Conference on Mobile Computing and Networking (MobiCom), 2012)
Many networked applications that run in the background on a mobile device incur significant energy drains when using the cellular radio interface for communication. This is mainly due to the radio-tail, where the cellular radio remaining in a high energy state for up to 20s after each communication spurt. In order to cut down energy consumption, many recent devices employ fast dormancy, a feature that forces the client radio to quickly go into a low energy state after a fixed short idle period. However, aggressive idle timer values for fast dormancy can increase signaling overhead due to frequent state transitions, which negatively impacts the network. In this work, we have designed and implemented RadioJockey, a system that uses program execution traces to predict the end of communication spurts, thereby accurately invoking fast dormancy without increasing network signaling load. We evaluate RadioJockey on a broad range of background applications and show that it achieves 20-40% energy savings with negligible increase in signaling overhead compared to fixed idle timer-based approaches.